2021
DOI: 10.11648/j.ijbbmb.20210601.12
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Growth Performance Evaluation of Agroforestry Tree Species in Babille District, East Hararghe Zone, Oromia, Ethiopia

Abstract: Study was under taken on five agroforestry tree species: Moringa oliefera, Gravilea robusta, Azadarichta indica, Leuceana leucocephala and Cordia africana at Fedis Agricultural Research Center to evaluate their adaptability and growth performance. The experiment was laid out in RCBD with three replications. The growth parameters; diameter, plant height and survival rate were measured and recorded at interval of three months. Results revealed that there were selected agroforestry tree species had no problem on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(3 reference statements)
2
0
0
Order By: Relevance
“…Hence, the plant heights of Olea europea, Moringa oleifera, and Calliandra calothyrsus were 1.48 m, 3.24 m, and 2.01 m respectively. The study was in line with the findings of [25] reported that the height of Moringa oleifera was 2.917m in Babille district, east Hararghe. Likewise, the study from [22] also reported that the height of Moringa oleifera was 3.97 m in Bako conditions.…”
Section: Plant Heightsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the plant heights of Olea europea, Moringa oleifera, and Calliandra calothyrsus were 1.48 m, 3.24 m, and 2.01 m respectively. The study was in line with the findings of [25] reported that the height of Moringa oleifera was 2.917m in Babille district, east Hararghe. Likewise, the study from [22] also reported that the height of Moringa oleifera was 3.97 m in Bako conditions.…”
Section: Plant Heightsupporting
confidence: 92%
“…Following this, the diameter at breast height of Olea europea, Moringa oleifera, and Calliandra calothyrsus in the final year of the study period were 1.94 cm, 3.72 cm, and 2.12 cm respectively. The result was similar to the findings of [25] reported that the DBH of Moringa oleifera was 2.85 cm in Babille district, east Hararghe, and DBH of Moringa oleifera was 4.92 cm in Bako conditions [22].…”
Section: Diameter At Breast Height (Dbh)supporting
confidence: 90%